Sex differences in the impact of frailty in elderly outpatients with heart failure - Díez-Villanueva, Pablo; Jiménez-Méndez, César; Bonanad, Clara; Ortiz-Cortés, Carolina; Barge-Caballero, Eduardo; Goirigolzarri, Josebe; Esteban-Fernández, Alberto; Pérez-Rivera, Angel; Cobo, Marta; Sanz-García, Ancor; Formiga, Francesc; Ariza-Solé, Albert; et al. (Frontiers in Cardiovascular Medicine, 2022)
Introduction Frailty is common among patients with heart failure (HF). Our aim was to address the role of frailty in the management and prognosis of elderly men and women with HF. Methods and results Prospective multicenter registry that included 499 HF outpatients ≥75 years old. Mean age was 81.4 ± 4.3 years, and 193 (38%) were women. Compared with men, women were older (81.9 ± 4.3 vs. 81.0 ± 4.2 years, p = 0.03) and had higher left ventricular ejection fraction (46 vs. 40%, p < 0.001) and less ischemic heart disease (30 vs. 57%, p < 0.001). Women had a higher prevalence of frailty (22 vs. 10% with Clinical Frailty Scale, 34 vs. 15% with FRAIL, and 67% vs. 46% with the mobility visual scale, all p-values < 0.001) and other geriatric conditions (Barthel index ≤90: 14.9 vs. 6.2%, p = 0.003; malnutrition according to Mini Nutritional Assessment Short Formulary ≤11: 55% vs. 42%, p = 0.007; Pfeiffer cognitive test's errors: 1.6 ± 1.7 vs. 1.0 ± 1.6, p < 0.001; depression according to Yesavage test; p < 0.001) and lower comorbidity (Charlson index ≥4: 14.1% vs. 22.1%, p = 0.038). Women also showed worse self-reported quality of life (6.5 ± 2.1 vs. 6.9 ± 1.9, on a scale from 0 to 10, p = 0.012). In the univariate analysis, frailty was an independent predictor of mortality in men [Hazard ratio (HR) 3.18, 95% confidence interval (CI) 1.29–7.83, p = 0.012; HR 4.53, 95% CI 2.08–9.89, p < 0.001; and HR 2.61, 95% CI 1.23–5.43, p = 0.010, according to FRAIL, Clinical Frailty Scale, and visual mobility scale, respectively], but not in women. In the multivariable analysis, frailty identified by the visual mobility scale was an independent predictor of mortality (HR 1.95, 95% CI 1.04–3.67, p = 0.03) and mortality/readmission (HR 2.06, 95% CI 1.05–4.04, p = 0.03) in men. Conclusions In elderly outpatients with HF frailty is more common in women than in men. However, frailty is only associated with mortality in men.